Efficacy of pulsed dye laser in granuloma annulare. - Bertlich, R.; Bertlich, M.; Bertlich, I.; Bertlich, M. (European Journal of Pediatric Dermatology, 2023)
Disseminated granuloma annulare is a benign, but difficult-to-treat entity without specific therapy guidelines. When it affects children, therapy options are more restricted because possible side effects of therapy have to be weighed against therapy benefit especially strictly. In this case, we successfully treated a young girl with very therapy refractory disseminated granuloma annulare with pulsed dye laser. For the first time in this patients’ history, the lesions improved markedly. The patient did not suffer any side effects and was very satisfied with the outcome.